From eurocentric territorial heritage to decolonial territorial-patrimonio. Epistemic turn from the South - Batista da Costa , Everaldo (2024)
This theoretical work aims to confront two debates on heritage developed on both sides of the Atlantic (Europe and Latin America), respectively, territorial heritage (Eurocentred) and territorial-patrimonio (decolonial). Methodologically, [1] explains the origin of the concept “territorial heritage” developed by the Spanish geographer J. Ortega Valcárcel and the Italian urban planner A. Magnaghi; [2] presents the Latin American “territorial-patrimonio” concept [proposed by the Brazilian geographer E. B. Costa]; and [3] recognizes the analytical derivations made by other authors, based on the two original proposals. In addition to clarifying the border between the two perspectives (with different epistemic matrices and praxis), the study defends a shift in thinking about vulnerable sites and subalternized and humiliated subjects in the long formative-territorial duration of Latin American countries.